The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21470/1678-9741-2017-0148
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Coronary Artery Bypass Graft Surgery in Patients with Mild Preoperative Renal Insufficiency

Abstract: IntroductionPreoperative renal insufficiency is an independent predictor of mortality after coronary artery bypass graft (CABG) surgery. However, there are few reports aimed to evaluate the impact of mild preoperative renal insufficiency on long-term follow-up outcomes after isolated CABG surgery. This study investigates the effect of mild preoperative renal insufficiency on long-term follow-up outcomes of patients after CABG.MethodsFive hundred eighty-four patients' data that underwent CABG between 1 January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The univariate factor analysis manifested that the 2 propensity score-matched groups had similar in-hospital outcomes, including surgical mortality, myocardial infarction, stroke, respiratory failure, pneumonia, redo for bleeding, RBC transfusion, DSWI, low cardiac output syndrome, IABP application, except the rates and severity of AKI. The same result was obtained by Weitie Wang et al, they reported older patients with mild preoperative RD had a higher mortality rate than normal patients in long-term survival, whereas no evidence of worse in-hospital mortality rate was found [10]. Jyrala et al who analyzed a cohort of 885 patients with or without mild preoperative RD received on-pump cardiac surgery, with respect to short- and long-term outcomes [11].…”
Section: Discussionsupporting
confidence: 57%
“…The univariate factor analysis manifested that the 2 propensity score-matched groups had similar in-hospital outcomes, including surgical mortality, myocardial infarction, stroke, respiratory failure, pneumonia, redo for bleeding, RBC transfusion, DSWI, low cardiac output syndrome, IABP application, except the rates and severity of AKI. The same result was obtained by Weitie Wang et al, they reported older patients with mild preoperative RD had a higher mortality rate than normal patients in long-term survival, whereas no evidence of worse in-hospital mortality rate was found [10]. Jyrala et al who analyzed a cohort of 885 patients with or without mild preoperative RD received on-pump cardiac surgery, with respect to short- and long-term outcomes [11].…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies mostly focused on the patients of renal insufficiency to verify the important regulatory role of preop-eGFR [ 12 , 13 , 15 ]. High preop-eGFR levels have also been connected with greater mortality among nonsurgical patients indicating a potential U-shaped association of preop-eGFR with poor prognosis [ 26 – 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mostly focused on the patients of renal insufficiency to verify the important regulatory role of preop-eGFR [12][13]15]. High preop-eGFR levels have also been connected with greater mortality among nonsurgical patients indicating a potential U-shaped association of preop-eGFR with poor prognosis [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that preop-eGFR is a moderately effective predictor of thirty-day mortality in hospitalized surgical patients [4]. However, the current research population is mainly concentrated on patients who have undergone critical surgery such as cardiac surgery [6] [7][8] [9][10] [11][12][13][14], lack of other surgeries. The ethnicity of these studies is also rarely related to Asians.…”
Section: Introductionmentioning
confidence: 99%